2011
DOI: 10.2478/s11533-011-0092-1
|View full text |Cite
|
Sign up to set email alerts
|

On (p, 1)-total labelling of 1-planar graphs

Abstract: A graph is 1-planar if it can be drawn on the plane so that each edge is crossed by at most one other edge. In this paper, it is proved that the (p, 1)-total labelling number of every 1-planar graph G is at most Δ(G) + 2p − 2 provided that Δ(G) ≥ 8p+4 or Δ(G) ≥ 6p+2 and g(G) ≥ 4. As a consequence, the well-known (p, 1)-total labelling conjecture has been confirmed for some 1-planar graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The lower bound for the maximum degree in this result was recently improved to 4p + 4 by Sun and Wu [14]. For 1-planar graphs, Zhang, Yu and Liu [21] proved the following result. Let ϕ be a function from E(G) to {1, 2, .…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The lower bound for the maximum degree in this result was recently improved to 4p + 4 by Sun and Wu [14]. For 1-planar graphs, Zhang, Yu and Liu [21] proved the following result. Let ϕ be a function from E(G) to {1, 2, .…”
Section: Introductionmentioning
confidence: 85%
“…A critical (p, 1)-total k-labelled graph is a graph G such that it admits no (p, 1)-total k-labelling, and any proper subgraph of G has a (p, 1)-total k-labelling. Zhang, Yu and Liu [21] proved the following two structural theorems for the critical (p, 1)-total labelled graph. Remark: the original statements of Lemmas 6 and 7 in [10] are not as the same as the above two ones.…”
Section: (P 1)-total Labellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of 1-planarity was introduced by Ringel [14], who proved that each 1-planar graph is vertex 7-colorable. This is the first result on the colorings of 1-planar graphs, and from then on, many authors started to investigate the coloring problems (see [1,3,4,6,15,16,17,21,23,24]) and the structural properties (see [5,8,9,10,11,13,18,19,20,22]) of 1-planar graphs. One of possible approaches in the study of local graph structures can be formalized in the following way (see [12]):…”
Section: V) a K- Kmentioning
confidence: 99%
“…Zhang et al showed that each 1-planar graph G with maximum degree ∆ is ∆-edge-colorable if ∆ ≥ 10 [25], or ∆ ≥ 9 and G contains no chordal 5-cycles [19], or ∆ ≥ 8 and G contains no chordal 4-cycles [20], or ∆ ≥ 7 and G contains no 3-cycles [21], is (∆ + 1)-edge-choosable and (∆ + 2)-total-choosable if ∆ ≥ 16 [27], is ∆-edge-choosable and (∆ + 1)-total-choosable if ∆ ≥ 21 [27]. Zhang et al also showed that the (p, 1)-total labelling number of each 1-planar graph G is at most ∆(G) + 2p − 2 if ∆(G) ≥ 8p + 4 [28], and the linear arboricity of each 1-planar graph G is exactly ∆(G)/2 if ∆(G) ≥ 33 [24].…”
Section: Introductionmentioning
confidence: 99%